Analysis of Environmental Impact Management on C Quarry Mining in Tiron Village, Banyakan District - ROMADHON , Romadhon (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to analyze the environmental impacts of C quarry mining in Tiron Village, Banyakan District, and propose appropriate measures for environmental management. The study uses a quantitative approach with a descriptive method. The quantitative approach is employed to test hypotheses using numerical data, while the descriptive method is used to describe and analyze the collected data. The population of this research includes all stakeholders involved in C quarry mining in Tiron Village, Banyakan District. The sample is determined using purposive sampling, selecting respondents with relevant knowledge and experience related to the research. The research instrument used is a questionnaire to measure respondents' perceptions of the impacts of C quarry mining. The validity and reliability of the questionnaire are tested using Pearson correlation and Cronbach's alpha reliability tests, respectively. Data collection is done by distributing questionnaires directly to the respondents. The collected data are analyzed using statistical tests. The findings of this research will provide valuable insights into the environmental impacts of C quarry mining in Tiron Village, Banyakan District. The results will contribute to developing effective environmental management strategies to mitigate the adverse effects of mining activities. This research highlights the importance of sustainable mining practices and the need for collaboration between various stakeholders to protect the environment and ensure the continuity of development projects.